2024
DOI: 10.1149/2162-8777/ad28c8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Current Density Pulses on Performance Enhancement of Optoelectronic Devices

Md Hafijur Rahman,
Nicholas Glavin,
Aman Haque
et al.

Abstract: Thermal annealing is commonly used in fabrication processing and/or performance enhancement of electronic and opto-electronic devices. In this study, we investigate an alternative approach, where high current density pulses are used instead of high temperature. The basic premise is that the electron wind force, resulting from the momentum loss of high-energy electrons at defect sites, can mobilize and eliminate internal defects. The proposed technique is demonstrated on commercially-available optoelectronic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This approach is supported by our previous research, which demonstrated the efficacy of EWF in mitigating postmanufacturing defects, resulting in enhanced forward current at a given voltage in pristine devices. 35) In our previous study, we have also demonstrated the efficacy of EWF assisted low-temperature processing in defect mitigation of metals and alloys. 36) Here, we extend our investigation to intentionally degraded devices, assessing EWF's effectiveness in defect mitigation within semiconductor devices, thus providing a comprehensive strategy for ensuring the longevity and reliability of these components in practical scenarios.…”
mentioning
confidence: 89%
“…This approach is supported by our previous research, which demonstrated the efficacy of EWF in mitigating postmanufacturing defects, resulting in enhanced forward current at a given voltage in pristine devices. 35) In our previous study, we have also demonstrated the efficacy of EWF assisted low-temperature processing in defect mitigation of metals and alloys. 36) Here, we extend our investigation to intentionally degraded devices, assessing EWF's effectiveness in defect mitigation within semiconductor devices, thus providing a comprehensive strategy for ensuring the longevity and reliability of these components in practical scenarios.…”
mentioning
confidence: 89%
“…By employing low frequency and narrow pulse widths, we successfully minimize thermal effects, maintaining the average temperature below 100 • C, even at an elevated current density of 3.35 × 10 5 A cm 2 . The use of short pulse width and low frequency provides sufficient time for heat to dissipate before the next pulse, minimizing the risk of excessive Joule heating [25,36,37]. This approach offers a more controlled exploration of how electropulsing can be optimized to exploit the beneficial aspects of EWF while mitigating the potential drawbacks of excessive Joule heating, thereby advancing our ability to distinguish between the thermal and athermal contributions to stress mitigation in electropulsing treatments.…”
Section: Introductionmentioning
confidence: 99%